2003
DOI: 10.1007/s00429-003-0328-3
|View full text |Cite
|
Sign up to set email alerts
|

Placentation in the alpaca Lama pacos

Abstract: Reproduction in South American camelids is poorly studied. To extend our knowledge of the development and cellular physiology of the placenta in the alpaca Lama pacos, we have examined specimens from day 150 of pregnancy to term. Morphological investigations using light, transmission and scanning electron microscopy, the histochemical localization of iron, alkaline and acid phosphatase activity, and the immunodetection of placental lactogen hormone were performed. Throughout pregnancy there was a progressive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 65 publications
4
30
1
13
Order By: Relevance
“…Generally speaking, the morphological and histochemical characteristics of the areolae in our study were very similar to those described in peccaries (Santos 2006), sows (Dantzer 1984) and alpacas (Olivera 2002, Olivera et al 2003a. The classification of regular and irregular areolae as observed in sows was not found in the llama (Abd-Elnaeim et al 2003).…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionsupporting
confidence: 85%
See 4 more Smart Citations
“…Generally speaking, the morphological and histochemical characteristics of the areolae in our study were very similar to those described in peccaries (Santos 2006), sows (Dantzer 1984) and alpacas (Olivera 2002, Olivera et al 2003a. The classification of regular and irregular areolae as observed in sows was not found in the llama (Abd-Elnaeim et al 2003).…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionsupporting
confidence: 85%
“…Both uni-and binucleated cells of the trophoblastic layer exhibited PAS-positive reactivity similar to that observed in dromedaries and alpacas (Jones et al 2000, Olivera et al 2003a. Acid phosphatase enzyme reactivity was observed in some trophoblastic cells localized, mainly localized at the top of the chorionic projections, differing from that found in the alpacas where this reactivity was only noted in the trophoblastic cells related to the areolae (Olivera et al 2003a). The PAS and acid phosphatase reactions showed that the trophoblastic cells actively participate in the uptake of products coming from the maternal surface, as well as in their metabolism and catalysis.…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionsupporting
confidence: 64%
See 3 more Smart Citations